Pengembangan LKPD Berbasis Discovery Learning dalam Mata Pelajaran IPAS Materi Indonesiaku Kaya Raya Kelas V Sekolah Dasar Negeri 34 Pontianak Selatan - Magdalena, Magdalena; Kartono, Kartono; Pranata, Rio (ISLAMIKA, 2025)
This study aims to produce a product of discovery learning-based student worksheets on the material of my rich Indonesia in grade V elementary school that is feasible. The research method used is research and development (R&D) by adapting the Thiagarajan 4D development model (define, design, development, and dissemination). The data source of this research is the validation result from one validator, and teacher response questionnaire. The data collection techniques were validation instruments and teacher response questionnaires. The results showed that during the research conducted using four stages of define, design, development and dissemination. The level of validity of the learner worksheet based on the results of didactic expert assessment with an average of 4.07 with the category “good”, construction 4 “good” and technical 4.5 “good”. Furthermore, the response from the teacher obtained an average of 4.91 in the “very good” category.